Urban Sprawl Symptoms in Bandar Lampung Suburban Area, Indonesia - Zulqadri Ansar; Walter Timo de Vries (Geoplanning: Journal of Geomatics and Planning)
This research investigates the phenomenon of urban sprawl in a medium-sized metropolitan area, specifically Bandar Lampung. It identifies the primary characteristics of urban sprawl and its impact on suburban development. The goal is to pinpoint the symptoms of urban sprawl through its spatial patterns, which may form systemically or sporadically, and predict their occurrence. The underlying theory is that urban sprawl symptoms can be observed in the rapid population growth and land use change in suburban areas. Using statistical and spatial analysis (Geographic Information System), we studied the population growth rate and land use alterations in Bandar Lampung and its suburbs over the past decade. Our study reveals that the population in the suburbs is growing faster than in the city. Over a decade, there has been a land use change to 1255 ha of built-up land. This change is strongly associated with the development of public infrastructure and road networks. We recommend implementing smart growth strategies to manage urban sprawl in medium-sized cities in Indonesia. Additionally, we provide a critical review of the causal relationships driving urban sprawl and its widespread impacts